The sheriffs of Savage Wells [large type] - Eden, Sarah M. (Thorndike Press large print clean reads, 2019)
"Paisley Bell is more than capable of being the sheriff of the sleepy town of Savage Wells--even if she is a woman. But when famed lawman Cade O'Brien arrives to take over the job, the two engage in a showdown of wits and skill. As sparks fly between the two sheriffs, Paisley is afraid she might not only lose her job, but also her heart."--Text from publisher.